The usage of various fungi species has allowed the Avicennia marina to develop more swiftly in Belawan and Pulau Sembilan - Yunasfi; Budi Utomo; Afifuddin Dalimunthe; Anita Zaitunah; Amanatul Fadhilah; Ipanna Enggar Susetya; O K Hasnanda Syahputra; Sri Lestari (Talenta Publisher, 2024)
Mangroves are a unique ecology that resides in places with salinity, which are inundated at low tide when there is no flooding and at high tide. Mangrove forests that are increasingly damaged cause the quality and quantity to decrease. Using different species of fungi that can accelerate the growth of mangroves is one attempt to increase and get high-quality mangrove seeds. This study aims to shed light on the fungi that can dramatically improve the growth of Avicennia marina seedlings. Mangroves can absorb organic and non-organic materials produced by decomposing microorganisms, which come from leaf litter or other decomposed materials. In this experiment, several fungal species were used, including Aspergillus niger, Aspergillus sp. 2, and Aspergillus sp. 1. The findings demonstrated that the fungus might speed up A. marina seedling growth. The plant's height, diameter, leaf width, and total dry weight were all altered as a result. Based on the study's findings, it can be said that Aspergillus niger provided the best growth for A. marina seedlings